Crown--First Nations relationships: a comparative analysis of the Tsawwassen Final Agreement and Tsilhqot'in v. British Columbia. - Hanna, Alan (2011)
This thesis explores contemporary Crown - First Nations relationships in British Columbia through a comparative analysis of the Tsawwassen First Nation Final Agreement and the court decision in Tsilhqot’in Nation v. British Columbia. The comparative analysis considers First Nations’ claims to land, rights and jurisdiction entering the processes of treaty and litigation with respect to how the claims are modified as a result. The reduction of land and limitations placed on claims through treaty and trial are indicative of the quality of the relationships the provincial Crown pursues with First Nations. Given the historic injustices of denying Aboriginal rights and title in BC, the province’s history of colonization requires a new relationship to be just and equitable. The Crown’s pursuit of economic certainty overwhelms the potential for justice to be achieved, which are both fundamental aspects requiring balance for a healthy relationship to be established. The outcome of the analysis reveals the Crown’s ongoing colonization of First Nations in British Columbia. As a result, this thesis attempts to offer a decolonized view of these relationships and some solutions for moving forward by placing the onus of responsibility squarely on the people of British Columbia to demand change from our provincial government. Graduate